Amivantamab plus lazertinib in osimertinib-relapsed EGFR-mutant advanced non-small cell lung cancer: a phase 1 trial - Cho, Byoung Chul; Kim, Dong-Wan; Spira, Alexander I.; Gomez, Jorge E.; Haura, Eric B.; Kim, Sang-We; Sanborn, Rachel E.; Cho, Eun Kyung; Lee, Ki Hyeong; Minchom, Anna; Lee, Jong-Seok; Han, Ji-Youn; et al. (Nature medicine, 2023)
Patients with epidermal growth factor receptor ( EGFR )-mutated non-small cell lung cancer (NSCLC) often develop resistance to current standard third-generation EGFR tyrosine kinase inhibitors (TKIs); no targeted treatments are approved in the osimertinib-relapsed setting. In this open-label, dose-escalation and dose-expansion phase 1 trial, the potential for improved anti-tumor activity by combining amivantamab, an EGFR-MET bispecific antibody, with lazertinib, a third-generation EGFR TKI, was evaluated in patients with EGFR -mutant NSCLC whose disease progressed on third-generation TKI monotherapy but were chemotherapy naive (CHRYSALIS cohort E). In the dose-escalation phase, the recommended phase 2 combination dose was established; in the dose-expansion phase, the primary endpoints were safety and overall response rate, and key secondary endpoints included progression-free survival and overall survival. The safety profile of amivantamab and lazertinib was generally consistent with previous experience of each agent alone, with 4% experiencing grade ≥3 events; no new safety signals were identified. In an exploratory cohort of 45 patients who were enrolled without biomarker selection, the primary endpoint of investigator-assessed overall response rate was 36% (95% confidence interval, 22–51). The median duration of response was 9.6 months, and the median progression-free survival was 4.9 months. Next-generation sequencing and immunohistochemistry analyses identified high EGFR and/or MET expression as potential predictive biomarkers of response, which will need to be validated with prospective assessment. ClinicalTrials.gov identifier: NCT02609776 . The combination of a bispecific antibody against EGFR and MET with a tyrosine kinase inhibitor (TKI) in patients with TKI-relapsed, chemotherapy-naive, EGFR-mutated advanced NSCLC is safe and shows preliminary efficacy.